PRA: how it can be used in BRAC programmes - Sen, Rita; Tarannum, Sabah; Biswas, Parul Lata (BRAC, 2019)
This is a documentation of a training workshop on PRA. The broad objective of the workshop was to orient the Regional Managers of Rural Development Programme (RDP). It is expected that by the end of this workshop, all the participants would have a good level of understanding of PRA tools and techniques. They also would be able to identify the relevant/specific areas where PRA could be applied and to develop working action plan with the AMs, POs and PAs using PRA in their programme activities. The workshop was organized by the Research and Evaluation Division of BRAC and held at CDM, Rajendrapur on 15-22 January, 1996. Mr. Kamal Kar, participatory development consultant from India, facilitated the workshop. Dr. G. Samdani Fakir, Head of the Training Division, also facilitated the workshop for a part of the time. Out of Twenty four participants 21 were RMs and Sector Specialists from RDP and 3 Researchers from RED were attended the workshop. For the purpose of field practical, the participants were divided into four groups and four villages were chosen where four di1ferent types of RDP activities were in operation. On the last day each group presented their field activity reports in a session which was attended by the senior BRAC management. Some useful feedback came out as a result of this workshop these can be summarized as - l) PRA tools like Physical and social mapping, Wealth and Matrix Ranking, seasonal calander and Livelyhood Analysis can be used to identify target population and programmes. Information collection can be rapid and approptiate as a result of using these techniques. 2) Time line, Impact flowchart Livelyhood Analysis and Venn Diagram can be used to monitor, evaluate and implement programmes and assess their in1pact. 3) Participatory planning and all the tools mentioned above can also be used tor problem identification and planning.